عقیدہ ختم نبوت کے تہذیبی پہلو اور مسلم امہ کی ذمہ داریاں: The Civilizational Aspects of the Finality of Prophethood and Responsibilities of Muslim Ummah - Shakeel Muhammad Haqqani ,; Dr. Muhammad Riaz Mahmood, (Al-Amīr Research Journal for Islamic Studies, 2025)
This article aims to analyze the various dimensions of the belief in the Finality of Prophethood and its civilizational significance in Islamic thought. In this context, it is essential to identify the responsibilities of Muslims. Within Islamic teachings, the belief in the Finality of Prophethood holds a central position. It is one of the foundational tenets of Islam, and its preservation is the foremost duty of every Muslim. This belief is not only significant from a religious perspective but also exerts profound influence on Islamic civilization, society, arts, and literature. It has provided the Islamic way of life with a complete and comprehensive framework, wherein the role model of the Holy Prophet (PBUH) serves as an eternal beacon of guidance. This belief is not only a theological cornerstone but also a focal point for the intellectual and moral identity of Muslims. The acknowledgment of Prophet Muhammad (PBUH) as the last messenger laid the groundwork for the principles of Islamic civilization, shaping its collective ethos, social structure, and ethical norms. Considering the fundamental importance of this belief in Islamic thought, there is a pressing need to explore its civilizational aspects and delineate the responsibilities it entails for the Muslim Ummah. This analysis is a crucial endeavor for academic circles, addressing both intellectual and civilizational imperatives. It is in light of this scholarly and civilizational necessity that the topic under discussion has been chosen for this research paper. Key words: Civilizational Responsibilities, Finality of Prophethood, Holy Prophet (PBUH), Islamic thought, Muslim Ummah